Synthetic switch-based baculovirus for transgene expression control and selective killing of hepatocellular carcinoma cells - Lin, Mei-Wei; Tseng, Yen-Wen; Shen, Chih-Che; Hsu, Mu-Nung; Hwu, Jih-Ru; Chang, Chin-Wei; Yeh, Chung-Ju; Chou, Min-Yuan; Wu, Jaw-Ching; Hu, Yu-Chen (Nucleic acids research, 2018)
Abstract Baculovirus (BV) holds promise as a vector for anticancer gene delivery to combat the most common liver cancer-hepatocellular carcinoma (HCC). However, in vivo BV administration inevitably results in BV entry into non-HCC normal cells, leaky anticancer gene expression and possible toxicity. To improve the safety, we employed synthetic biology to engineer BV for transgene expression regulation. We first uncovered that miR-196a and miR-126 are exclusively expressed in HCC and normal cells, respectively, which allowed us to engineer a sensor based on distinct miRNA expression signature. We next assembled a synthetic switch by coupling the miRNA sensor and RNA binding protein L7Ae for translational repression, and incorporated the entire device into a single BV. The recombinant BV efficiently entered HCC and normal cells and enabled cis-acting transgene expression control, by turning OFF transgene expression in normal cells while switching ON transgene expression in HCC cells. Using pro-apoptotic hBax as the transgene, the switch-based BV selectively killed HCC cells in separate culture and mixed culture of HCC and normal cells. These data demonstrate the potential of synthetic switch-based BV to distinguish HCC and non-HCC normal cells for selective transgene expression control and killing of HCC cells.